Cultural differences in the organization of research article introductions from the field of educational psychology: English and Chinese - Loi, Chek Kim; Moyra Sweetnam Evans (2010)
This paper investigates the rhetorical organization of the introduction sections of English and Chinese research articles in the field of educational psychology. The study reported in this paper adopts Swales’s (1990, 2004) framework of move analysis. In general, the findings of the present study reveal that there are similarities and differences between English and Chinese research article introductions in terms of the employment of moves and steps. It is suggested that the rhetorical differences reflect some of the distinctive characteristics of the two different cultures, English and Chinese. The findings of the present study have both theoretical and pedagogical implications.